2020
DOI: 10.3390/microorganisms9010053
|View full text |Cite
|
Sign up to set email alerts
|

Is Gut Microbiota Dysbiosis a Predictor of Increased Susceptibility to Poor Outcome of COVID-19 Patients? An Update

Abstract: The scientific knowledge already attained regarding the way severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infects human cells and the clinical manifestations and consequences for Coronavirus Disease 2019 (COVID-19) patients, especially the most severe cases, brought gut microbiota into the discussion. It has been suggested that intestinal microflora composition plays a role in this disease because of the following: (i) its relevance to an efficient immune system response; (ii) the fact that 5–10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 86 publications
(159 reference statements)
2
38
0
Order By: Relevance
“…The microbiome in these patients is predominantly composed of harmful organisms, such as Streptococcus, Rothia, Veilonella, and Actinomyces, and decreased levels of beneficial symbionts, including Agathobacter, Fusicatenibacter, Roseburia, and Ruminococcaceae. In addition, a significant correlation was observed between microbial composition and COVID-19 severity; whereas microbiota that positively correlated with disease severity belonged to harmful organisms, such as Firmicutis, Coprobacillus, and Clostridium spp., beneficial microbiota, including Alistipes ondedonkii and Faecalibacterium prausnitzii negatively correlated with COVID-19 severity (Ferreira et al, 2021).…”
Section: Microbiome Composition and Diversity In Covid-19mentioning
confidence: 95%
See 1 more Smart Citation
“…The microbiome in these patients is predominantly composed of harmful organisms, such as Streptococcus, Rothia, Veilonella, and Actinomyces, and decreased levels of beneficial symbionts, including Agathobacter, Fusicatenibacter, Roseburia, and Ruminococcaceae. In addition, a significant correlation was observed between microbial composition and COVID-19 severity; whereas microbiota that positively correlated with disease severity belonged to harmful organisms, such as Firmicutis, Coprobacillus, and Clostridium spp., beneficial microbiota, including Alistipes ondedonkii and Faecalibacterium prausnitzii negatively correlated with COVID-19 severity (Ferreira et al, 2021).…”
Section: Microbiome Composition and Diversity In Covid-19mentioning
confidence: 95%
“…Given the recent advent of the SARS-CoV-2 infection, the relationship between COVID-19 severity and microbiome diversity and composition is emerging. Recent reports have demonstrated that gut microbiota composition and diversity is significantly altered in patients with COVID-19 who harbored significantly dysbiotic microbiota composition when compared to healthy individuals (Reviewed in Ferreira et al, 2021). The microbiome in these patients is predominantly composed of harmful organisms, such as Streptococcus, Rothia, Veilonella, and Actinomyces, and decreased levels of beneficial symbionts, including Agathobacter, Fusicatenibacter, Roseburia, and Ruminococcaceae.…”
Section: Microbiome Composition and Diversity In Covid-19mentioning
confidence: 99%
“…On the other hand, Clostridia spp. showed a negative correlation [62]. Interestingly, a strong association was demonstrated between the severity of COVID-19 in the elderly and such bugs and the blood proteomics risk score (PRS).…”
Section: Potential Gut Microbiota Modulation In Critically Ill Patient With Sars-covmentioning
confidence: 99%
“…Additionally, lymphopenia may be associated with glucocorticoids treatment (51). Since gut microbiota is one of the key components of the host immune system, and primary responses to infections and other immune insults, lymphopenia due to SARS-CoV-2 infection may interfere and predispose to changes in the normal flora by opportunistic germs (52)(53)(54)(55).…”
Section: Immune Responsementioning
confidence: 99%